EFEKTIFITAS SENAM NIFAS DAN TEKNIK RELAKSASI TERHADAP INVOLUSI UTERUS PADA PASCA- SALIN NORMAL - Indreswati Indreswati; Annisa Annisa (Maternal Child Health Care, 2021)
Maternal Mortality Rate (MMR) is an indicator of health status. However, in reality the problem of maternal mortality and morbidity in Indonesia is still a big problem. Maternal mortality occurs due to several factors. One of them is hemorrhage 30.3%. Postpartum hemorrhage is caused by uterine atony 70%, trauma 20%, and rest placenta 10%. Uterine atony can be prevented through postpartum exercise and relaxation techniques. This study aimed to determine The Effectiveness of Postpartum Exercise and Relaxation Techniques on Uterine Involution in Normal Post-Copy Mothers in Gedang Community Health Center Working Area in 2020.It was Quasi Experimental Research (quasi-experimental) with posttest only design with two comparison treatment. The population was all postpartum mothers with normal delivery on November 2020. Total sampling technique had been used to choose the samples. The data were collected through direct observations by using observation sheet instrument. The data were analyzed by Mann Whitney test.The results showed that in the group given postpartum exercise intervention 14.50> the group that was given postpartum exercise intervention and relaxation techniques. It means that the subinvolution score was greater. Mann Whitney test ρ<0.05, it indicates that the mean rank difference between the two groups was significant. In short, postpartum exercise and relaxation technique were effective in accelerating the process of uterine involution.Last, it is suggested to the midwives to improve and perform midwifery services by applying postpartum exercise methods and relaxation techniques to make the uterine involution process runs well. Keywords    : The Effectiveness, Postpartum Exercise, Relaxation TechniquesReferences  : 26 (2004-2019)